Control of the collateral formation of cardiovascular disease by SRPK1 - Bhalla, Sohni Ria (2021)
Vascular insufficiency in peripheral arterial disease (PAD) results in tissue ischemia. In response, circulating monocytes produce vascular endothelial growth factor (VEGF-A), a key regulator of angiogenesis. Patients with PAD and mouse models of ischemic disease have reduced soluble frizzled related protein (Sfrp5) resulting in increased wingless-type MMTV integration site family 5a (Wnt5a) activity. Monocytes from both humans and mice overexpress the anti-angiogenic VEGF-A isoform, VEGF-A165b. VEGF splicing is regulated by the phosphorylation of serine/arginine splicing factors (SRSFs) by splicing factor kinases such as serine-arginine protein kinase 1 (SRPK1). The role of SRPK1 has been shown in multiple cell types, but the role in monocytes is unknown. Therefore, this thesis investigated the effect of SRPK1 on revascularisation using experimental hind limb ischemia (HLI) in a transgenic mouse model with monocyte specific Wnt5a overexpression (LysM-Wnt5aGain of Function) administered with an SRPK1 inhibitor. To determine the role of SRPK1 specifically in the monocytes, a novel double transgenic mouse model was generated with Wnt5a hyperactivity and SRPK1 knockout.